Sous Chef Efforts to Improve Hot Kitchen Product Quality: Upaya Sous Chef dalam Meningkatkan Kualitas Produk Hot Kitchen - Setiari, Ni Kadek Nanik; Sunata, I Made; Karina Putri, Ida Ayu (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2026)
Product quality is a critical determinant of restaurant competitiveness because it shapes guest satisfaction, repeat visits, and the reputation of food and beverage operations. This study analyzes the efforts of the sous chef to improve hot kitchen product quality at The Barn Restaurant Canggu Bali. The research used a qualitative descriptive approach with data collected through observation, interviews, documentation, and review of guest comments. The analysis focused on three aspects: the role of the sous chef in improving hot kitchen products, operational constraints affecting product quality, and corrective efforts implemented to overcome those constraints. The results show that the sous chef’s role is reflected in the supervision of raw material selection, control of cooking processes, coordination of hot kitchen personnel, and evaluation of the final product before service. The main constraints were inconsistent raw material quality, weak teamwork during peak operational hours, uneven cooking skills, and guest comments related to menu variety and taste consistency. Corrective efforts included stricter raw material checking, daily briefing, clearer work allocation, control of seasoning and cooking methods, informal staff coaching, improved hygiene and sanitation discipline, and staff appreciation. The study concludes that sous chef leadership is not only technical but also managerial because product quality depends on continuous coordination, standardization, staff development, and final product evaluation in daily kitchen operations.